Economics, Public Policy, and Law - Rose-Ackerman, Susan (Victoria University of Wellington Law Review, 1996)
Some lawyers view the law as a self-contained body of wisdom independent of the contaminating influences of other branches of knowledge. Such lawyers resist efforts to combine law with economics. In doing so, the author argues that these lawyers miss an opportunity for gaining a deeper understanding of the way law works in the world. This article thus explores the relationship between economics as a methodology, public policy, and the law. The author first tackles the argument that the economist’s concentration on efficiency is flawed because it is unconcerned with justice. The author then discusses the role of economics in light of collective decision-making found throughout society. Economics and the design of efficient regulatory schemes are also discussed, as well as in the comparative law context. It is argued that the intersection between the common law and economics must be widely accepted, even though it suffers from limitations in resolving difficult policy issues. Thus, the author concludes that economic analysis alone cannot be an all-purpose resolver of the problems of the modern capitalist welfare state. Nonetheless, economic frameworks remain useful for lawyerly thinking; law and economics must thus be joined by a broader range of subjects, including political science and public administration.